Some Hadamard–Fejér Type Inequalities for LR-Convex Interval-Valued Functions - Muhammad Bilal Khan; Savin Treanțǎ; Mohamed S. Soliman; Kamsing Nonlaopon; Hatim Ghazi Zaini (Fractal and Fractional, 2021)
The purpose of this study is to introduce the new class of Hermite–Hadamard inequality for LR-convex interval-valued functions known as LR-interval Hermite–Hadamard inequality, by means of pseudo-order relation ( <semantics>≤p</semantics> ). This order relation is defined on interval space. We have proved that if the interval-valued function is LR-convex then the inclusion relation “ <semantics>⊆</semantics> ” coincident to pseudo-order relation “ <semantics>≤p</semantics> ” under some suitable conditions. Moreover, the interval Hermite–Hadamard–Fejér inequality is also derived for LR-convex interval-valued functions. These inequalities also generalize some new and known results. Useful examples that verify the applicability of the theory developed in this study are presented. The concepts and techniques of this paper may be a starting point for further research in this area.